Evaluation and Impact of ASPIRE: An Interactive Tobacco Prevention Curriculum among University Students in India - Vishwakarma, Gayatri; Singh, Sohini; Marani, Salma K; Arya, Ashish; Calabro, Karen; Gupta, Garima; Mehta, Anurag; Alexander, V. (South Asian Journal of Cancer, 2021)
Online education approach provides innovative opportunities for engaging youths. Web-based, multimedia smoking prevention programs have been tested in high-income countries; however, efficacy of such programs is not well-investigated in low- and middle-income countries. The aim of this study was to evaluate the impact of A Smoking Prevention Interactive Experience (ASPIRE), an interactive tobacco prevention curriculum, among university students in India.A single-subject cohort study where each subject serves as their own control was conducted among university student participants engaged in ASPIRE, 60 minutes per week for five consecutive weeks during July to August of 2019. Assessments were conducted at baseline and immediately after exposure to ASPIRE. To evaluate the program, a structured instrument was specifically designed to measure the outcomes.A total of 103 university students participated voluntarily. Average age of the participants was 18.3±0.9 ranging from 17 to 20 years. Eighteen percent of students were curious to know about the various smoking products. More males were more susceptible to cigarette smoking as compared to females. The majority of participants felt that ASPIRE was culturally appropriate for young adults in India, but a modified version targeted toward Indian youth would be more acceptable. Pre- to postintervention knowledge of tobacco-related hazards increased from 70 to 97% (p < 0.001).ASPIRE, a multimedia interactive program, demonstrated its considerable potential to discourage smoking initiation among Indian youth.
Keywords: A Smoking Prevention Interactive Experience (ASPIRE); curiosity; smoking; knowledge; prevention